Who’s Afraid of the Lucky MOOSE? Canada’s Dangerous Self-Defence Innovation - Weisbord, Noah (McGill Law Journal / Revue de droit de McGill, 2018)
With little public discussion, the Canadian law of self-defence has become, in important respects, more permissive than Florida’s Stand Your Ground law. This article provides original historical research into the origins of the Canadian law of self-defence that reveals the evolution of its current conceptual features. It compares these features with the features of the Florida law and warns that in climates of fear, despite Canadian safeguards, Canada’s law is vulnerable to biased or unprincipled application. The Gerald Stanley case in Battleford Saskatchewan serves as a warning. The author argues that Stanley’s successful accident defence in the homicide of Colten Boushie was, in fact, predicated on dangerous notions of defence of property and defence of person that prioritize the protection of property, liberty, and honour over human life.